CORRELATION ANALYSIS OF NEURITE ORIENTATION DISPERSION & DENSITY IMAGING IN MND. Issue 12 (15th November 2016) - Broad, Rebecca; Gabel, Matthew; Dowell, Nicholas; Zhang, Gary; Alexander, Daniel; Cercignani, Mara; Leigh, Peter Nigel
Abstract : Background: Neurite Orientation Dispersion and Density Imaging (NODDI) is an established technique for estimating complexity of neuronal architecture.1 We used NODDI to characterise the neurodegenerative processes underlying motor neurone disease (MND), then correlated with regional brain volumes and clinical markers of disease. Methods: Diffusion-weighted and resting state fMRI scans were performed on 16 MND participants and 16 controls to yield measures of neurite orientation dispersion index (ODI), neurite density index (NDI), and Isotropic compartment (ISO). MND participants underwent clinical assessment of MND severity including medical research council (MRC) score and forced vital capacity (FVC). Pearson's correlation coefficient and its significance level was calculated for multiple combinations of imaging and clinical outcome measures. Results: Reduced ODI within the prefrontal cortex correlated with reduced FVC (P0.02). Within the corpus callosum increased ODI correlated with lower MRC score (P0.02), while higher ISO correlated with reduced volume (P0.007). In the para-hippocampal gyrus reduced ODI correlated with decreased volume (P0.01). Conclusion: NODDI demonstrates microstructural changes associated with MND. Correlation of NODDI parameters with certain regional brain volumes and clinical features of MND supports NODDI as a candidate imaging biomarker in MND.